1997
DOI: 10.1136/oem.54.6.443
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of nasal and bladder cancer to locate sources of exposure to occupational carcinogens.

Abstract: Objective-To locate sources of occupational exposure to nasal and bladder carcinogens for surveillance follow up in British Columbia, Canada. Methods-Incident cases of nasal cancer (n=48), bladder cancer (n=105), and population based controls (n=159) matched for sex and age, were interviewed about their jobs, exposures, and smoking histories. Odds ratios (ORs) were calculated for 57 occupational groups with stratified exact methods to control for age, sex, and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 42 publications
1
33
2
7
Order By: Relevance
“…However, we did not observe a consistent increase in the risk of esophageal cancer in our study. Neither could we confirm the excess risk of bladder cancer observed in US cohort studies of dry cleaners (4,5), and in US and Canadian case-referent studies of nonwhite dry cleaners, ironers, and pressers (23) and laundry personnel (24). Our negative results may be explained by differences in exposure circumstances between North America and Sweden, as well as by dilution due to the inclusion of launderers, who have less solvent exposure than dry cleaners.…”
Section: Discussioncontrasting
confidence: 69%
“…However, we did not observe a consistent increase in the risk of esophageal cancer in our study. Neither could we confirm the excess risk of bladder cancer observed in US cohort studies of dry cleaners (4,5), and in US and Canadian case-referent studies of nonwhite dry cleaners, ironers, and pressers (23) and laundry personnel (24). Our negative results may be explained by differences in exposure circumstances between North America and Sweden, as well as by dilution due to the inclusion of launderers, who have less solvent exposure than dry cleaners.…”
Section: Discussioncontrasting
confidence: 69%
“…Actually the main professions in the region are tertiary or farming. In two studies also mining and metal industry have been related to an increased risk of bladder cancer (14,23). Both have been major industries within the province, but outside the cluster region.…”
Section: Discussionmentioning
confidence: 99%
“…Past case-control and cohort studies have suggested an association with exposure to solvents and paints (5,(41)(42)(43). A recent study in the Netherlands found a nonsignificant excess for those exposed to paint components (33).…”
Section: Cases (N)mentioning
confidence: 99%